Inherited mutations in BRCA1 and BRCA2 in an unselected multiethnic cohort of Asian patients with breast cancer and healthy controls from Malaysia - Wen, Wei Xiong (J Med Genet, 2018)
BACKGROUND: Genetic testing for BRCA1 and BRCA2 is offered typically to selected women based on age of onset and family history of cancer. However, current internationally accepted genetic testing referral guidelines are built mostly on data from cancer genetics clinics in women of European descent. To evaluate the appropriateness of such guidelines in Asians, we have determined the prevalence of germ line variants in an unselected cohort of Asian patients with breast cancer and healthy controls. METHODS: Germ line DNA from a hospital-based study of 2575 unselected patients with breast cancer and 2809 healthy controls were subjected to amplicon-based targeted sequencing of exonic and proximal splice site junction regions of BRCA1 and BRCA2 using the Fluidigm Access Array system, with sequencing conducted on a Illumina HiSeq2500 platform. Variant calling was performed with GATK UnifiedGenotyper and were validated by Sanger sequencing. RESULTS: Fifty-five (2.1%) BRCA1 and 66 (2.6%) BRCA2 deleterious mutations were identified among patients with breast cancer and five (0.18%) BRCA1 and six (0.21%) BRCA2 mutations among controls. One thousand one hundred and eighty-six (46%) patients and 97 (80%) carriers fulfilled the National Comprehensive Cancer Network guidelines for genetic testing. CONCLUSION: Five per cent of unselected Asian patients with breast cancer carry deleterious variants in BRCA1 or BRCA2. While current referral guidelines identified the majority of carriers, one in two patients would be referred for genetic services. Given that such services are largely unavailable in majority of low-resource settings in Asia, our study highlights the need for more efficient guidelines to identify at-risk individuals in Asia.